Vasectomy and risk of prostate cancer: population based matched cohort study. (3rd November 2016) - Nayan, Madhur; Hamilton, Robert J; Macdonald, Erin M; Li, Qing; Mamdani, Muhammad M; Earle, Craig C; Kulkarni, Girish S; Jarvi, Keith A; Juurlink, David N
Abstract : Objective To determine the association between vasectomy and prostate cancer, adjusting for measures of health seeking behaviour. Design Population based matched cohort study. Setting Multiple validated healthcare databases in Ontario, Canada, 1994-2012. Participants 326 607 men aged 20 to 65 who had undergone vasectomy were identified through physician billing codes and matched 1:1 on age (within two years), year of cohort entry, comorbidity score, and geographical region to men who did not undergo a vasectomy. Main outcomes measures The primary outcome was incident prostate cancer. Secondary outcomes were prostate cancer related grade, stage, and mortality. Results 3462 incident cases of prostate cancer were identified after a median follow-up of 10.9 years: 1843 (53.2%) in the vasectomy group and 1619 (46.8%) in the non-vasectomy group. In unadjusted analysis, vasectomy was associated with a slightly increased risk of incident prostate cancer (hazard ratio 1.13, 95% confidence interval 1.05 to 1.20). After adjustment for measures of health seeking behaviour, however, no association remained (adjusted hazard ratio 1.02, 95% confidence interval 0.95 to 1.09). Moreover, no association was found between vasectomy and high grade prostate cancer (adjusted odds ratio 1.05, 95% confidence interval 0.67 to 1.66), advanced stage prostate cancer (adjusted odds ratio 1.04, 0.81 to 1.34), or mortality (adjusted hazard ratio 1.06, 0.60 to 1.85). Conclusion The findings do not support an independent association between vasectomy and prostate cancer.